Extraction and Stability of Betacyanin from Blood Leaf (Study on Water to Ethanol Ratio and Extraction Temperature) - Khuluq, Ahmad Dhiaul; Widjanarko, Simon Bambang; Murtini, Erni Sofia (Jurnal Teknologi Pertanian, 2007)
The aim of this research was to know the temperature’s influence and the solvent comparison (water:ethanol) on the betacyanin extract properties from blood leaf. The research was also aimed to know the stability of betacyanin extract toward temperature, pH, oxidant, and light of the best treatment. This research was conducted in two factorial randomized block design. The first factor was extraction temperature (4oC, 30oC and 60oC) and the second factor was water to ethanol ratio (8:2, 5:5, and 2:8 (v/v). Each treatment combination was conducted in triplication. The result of this research was analyzed using ANOVA, followed by 5% LSD test. If it had interaction, it would be continued by DMRT 5% test. The best treatment was tested using De Garmo effectiveness index. The best characteristic of extract was obtained from the water to ethanol ratio of 5:5 and extraction temperature of 30oC. Extract had physic-chemical properties as follows: betacyanin content of 45,81 mg/100 g, yield of 81,05%, ethanol residue of 0,099%, pH of 6,68, and color intensity L* of 24,4; a* of 4,7; and b* of 7,9. The stability of extract decreased as well as the increasing of heating temperature, oxidant concentration (H2O2), and duration of lamp rays radiation, and the extract stability increased at pH 5Keywords: Betacyanin, solvent, temperature, stability